Magneto‐Photoluminescence Based on Two‐Photon Excitation in Lanthanide‐Doped Up‐Conversion Crystal Particles. Issue 16 (20th February 2017) - Xu, Hengxing; Qin, Wei; Li, Mingxing; Wu, Ting; Hu, Bin
Abstract : Experimental studies on magneto‐photoluminescence based on two‐photon excitation in up‐conversion Y2 O2 S:Er, Yb crystal particles are reported. It is found that the up‐conversion photoluminescence generated by two‐photon excitation exhibits magnetic field effects at room temperature, leading to a two‐photon excitation‐induced magneto‐photoluminescence, when the two‐photon excitation exceeds the critical intensity. By considering the spin selection rule in electronic transitions, it is proposed that spin‐antiparallel and spin‐parallel transition dipoles with spin mixing are accountable for the observed magneto‐photoluminescence. Specifically, the two‐photon excitation generates spin‐antiparallel electric dipoles between 4 S3/2 – 4 I15/2 in Er 3+ ions. The antiparallel spins are conserved by exchange interaction within dipoles. When the photoexcitation exceeds the critical intensity, the Coulomb screening can decrease the exchange interaction. Consequently, the spin–orbital coupling can partially convert the antiparallel dipoles into parallel dipoles, generating a spin mixing. Eventually, the populations between antiparallel and parallel dipoles reach an equilibrium established by the competition between exchange interaction and spin–orbital coupling. Applying a magnetic field can break the equilibrium by disturbing spin mixing through introducing spin precessions, changing the spin populations on antiparallel and parallel dipoles and leading to the magneto‐photoluminescence. Therefore, spin‐dependent transition dipoles present a convenient mechanism to realize magneto‐photoluminescence in multiphoton up‐conversion crystal particles. Abstract : Magneto‐photoluminescence can be observed, when the two‐photon excitation exceeds the critical intensity 2080 mW cm −2 in up‐converting Y2 O2 S:Er, Yb crystals at room temperature. Spin‐dependent transition dipoles with operative spin mixing between antiparallel and parallel spins form the necessary condition to generate magneto‐photoluminescence in up‐conversion materials.